India in the 1980's and 1990's : A Triumph of Reforms - Panagariya, Arvind (IMF Working Papers; Working Paper ;, 2004)
Bradford DeLong and Dani Rodrik have argued that reforms in India cannot be credited with higher growth because the growth rate crossed the 5 percent mark in the 1980s, well before the launch of the July 1991 reforms. This is a wrong reading of the Indian experience for two reasons. First, liberalization was already under way during the 1980s and played a crucial role in stimulating growth during that decade. Second, growth in the 1980s was fragile and unsustainable. The more systematic and systemic reforms of the 1990s, discussed here in detail, gave rise to more sustainable growth. The paper concludes by explaining why the growth rate in India nevertheless continues to trail that of China.